The doubt factory - Bacigalupi, Paolo (Little, Brown and Company, 2014)
"When a radical band of teen activists claim that Alix's powerful father covers up wrongdoing by corporations that knowingly allow innocent victims to die in order to make enormous profits from unsafe products, she must decide if she will blow the whistle on his misdeeds"--